Modulation Function Calculation For Optical Semiconductor Fractal Modulator - Mohammad, AR. A. S.; Jabbar, A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The research  includes the study and calculation of the modulation function of Optical Semiconductor Fractal  Modulator and spatial frequency for different values of Silicon modulator transmittance percentage(10%,35%,45%,58%),it found the relation between the modulation function of Silicon and spatial frequency, the exponential relation of all values of the transmittance , the best state of modulation function when the value of transmittance is T=58% ,also the research includes the study of the relation of transmittance with different values of refractive index of Silicon . So the research involves building a computer program of output data which would relate to fractal optical modulation made of semiconductor material as shown in Fig. (1).